Koreografi Tari Nggainah Menjres di Sanggar LKP Merpati Kecamatan Blora Kabupaten Blora - Tarakamita Cakrawati; R.Indriyanto (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Nggainah Menjres Dance is one of the traditional folk dance works created by Mrs. Umi Ardiyah, the owner of the LKP Merpati Studio, in 2014. It was inspired by one of the characters from the Barongan folk tale of Blora Regency. The issue examined in this study is the choreography of the Nggainah Menjres Dance at the LKP Merpati Studio in Blora District, Blora Regency. The purpose of this research is to describe the choreography of the Nggainah Menjres Dance. The method used in this study is a descriptive qualitative approach combined with a choreographic approach. The data collection techniques for the Nggainah Menjres Dance include observation, interviews, and documentation. The results of the choreographic analysis of the Nggainah Menjres Dance cover both the process and the form of the choreography. The choreographic process includes exploration, improvisation, and composition. The choreographic form includes theme, title, work pattern, movement, number of dancers, accompaniment, floor pattern, makeup and costume, properties, stage form, and lighting. Based on the above findings, the Nggainah Menjres Dance is a form of dance artwork that correlates with the folk art of Blora and must continue to be preserved and developed as part of the region's artistic identity.